The innovative "NDBA" concrete safety barrier able to withstand two subsequent TB81 crash tests. (September 2020) - Dinnella, Nicola; Chiappone, Sandro; Guerrieri, Marco
Highlights: The new NDBA concrete road safety barrier is presented. Numerical simulations (LS-DYNA software) and full-scale crash tests have been performed. NDBA barrier is able to withstand two subsequent heavy vehicle (38 t) impacts. The new barrier may guarantee more safety for light vehicle occupants than a conventional steel safety barrier. Abstract: The new NDBA concrete road safety barrier is characterized by an innovative anchorage system based on two "C" steel profiles incorporated into the terminal sections of each module and a vertical HEM 100 steel profile inserted for linking the barrier modules. Every single barrier module is fixed in the body of the road embankment and pavement layers by six IPE 80 steel beams (three for each side with a mutual distance of 2 m), each 78 cm long. The IPE 80 steel beams are placed into niches, in the lower part of the barrier. The new barrier has been analysed first by numerical simulations (LS-DYNA software) and afterwards by full-scale crash tests. One TB11 (light vehicle) and two successive TB 81 (heavy vehicle) full-scale crash tests have been performed on NDBA barrier of 72 m length. The second TB81 test was performed on a damaged barrier previously subjected to impact without it being repaired. The experiments were conducted at "CSI test centre" in Bollate, Milan (Italy). According to the EN 1317 regulation, the results have shown a containment level CL = 725 kj (H4b class), a measured maximum ASI = 1.26 (class B), a working width W = 0.74 m (class W2). The research proves that the NDBA barrier is able to withstand two subsequent heavy vehicle (38 t) impacts. In addition, the study demonstrates that the new barrier may guarantee more safety for light vehicle occupants (TB11 test) than a conventional steel safety barrier with equal containment level (H4b class). Therefore, in the near future, NDBA barrier may be installed on existing roads, especially where reduced working width (W2) is required or in motorways with high AADT values and heavy vehicle percentage.